CHINA’S NATIONAL IMAGE: The Analysis of Chinese Tourists on New Media in Thailand - Tuzov, Viktor; Ansah, Patrick Owusu; Boonanant, Chanchanok (Department of Communication Science, Bakrie University, 2020)
This article comparatively analyzes the images of Chinese tourists on the news websites of Bangkok Post (E-Newspaper) and Channel 7 (E- media), to examine the tone of images of Chinese tourists on the websites of selected mainstream media in Thailand. The results showed a variety of discovery data of Chinese tourists' images happening in Thailand. When studying the national image of each country, it is regarded as a normal problem that the result came out both in a positive and negative way. Through the content analysis approach, this article reveals the basic framework of Chinese tourist behavior within and outside the national image, highlights the close relationship between tourism and national image-building. According to the findings, the frequent keywords that were mostly used and often appeared in news are negative words. The media agenda presented highly in Bangkok Post and Channel7 was the social agenda. Also, the political news received the lowest coverage in both Bangkok Post and Channel7 in regard to the chosen timeframe for the study. Overall, the social agenda was the most presented media agenda in both Bangkok Post and Channel7 To cite this article (7th APA style):Tuzov, V., Ansah, P. O. and Boonanant, C. (2020). China’s National Image: The Analysis of Chinese Tourists on New Media in Thailand. Journal Communication Spectrum, 10(1), 10-23. http://doi.org/10.36782/jcs.v10i1.1977